2023
DOI: 10.1186/s12916-022-02712-7
|View full text |Cite
|
Sign up to set email alerts
|

Associations between types and sources of dietary carbohydrates and cardiovascular disease risk: a prospective cohort study of UK Biobank participants

Abstract: Background Recent studies have reported that the associations between dietary carbohydrates and cardiovascular disease (CVD) may depend on the quality, rather than the quantity, of carbohydrates consumed. This study aimed to assess the associations between types and sources of dietary carbohydrates and CVD incidence. A secondary aim was to examine the associations of carbohydrate intakes with triglycerides within lipoprotein subclasses. Methods A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…We do not yet know if free grocery provision in acute coronary event recovery improves outcomes, or leads to a change in immediate or habitual dietary intakes. The trial is ongoing; therefore, results are not yet known, and no conclusion can be drawn at this time, however, higher dietary fibre and unsaturated fat intakes have been shown effective in the general population17 39 and for those with other NCDs 40 41. Undertaking this trial, however, is an opportunity to answer these research questions, and inform acute CHD management going forward.…”
Section: Discussionmentioning
confidence: 99%
“…We do not yet know if free grocery provision in acute coronary event recovery improves outcomes, or leads to a change in immediate or habitual dietary intakes. The trial is ongoing; therefore, results are not yet known, and no conclusion can be drawn at this time, however, higher dietary fibre and unsaturated fat intakes have been shown effective in the general population17 39 and for those with other NCDs 40 41. Undertaking this trial, however, is an opportunity to answer these research questions, and inform acute CHD management going forward.…”
Section: Discussionmentioning
confidence: 99%
“…, alternate Mediterranean diet [aMED], recommended food score [RFS], dietary approaches to stop hypertension [DASH] and Mediterranean-DASH Intervention for Neurodegenerative Delay [MIND] diet) using the average of at least two repeated 24 h dietary assessments. 24,25 Brief descriptions of the four dietary pattern scores are presented below, and comprehensive information on the compositions and scoring methods is shown in additional file 1: ESI Table 1 †…”
Section: Methodsmentioning
confidence: 99%
“…To deattenuate the effects of within-person variability and the coefficients for random error, we calculated the dietary pattern scores (i.e., alternate Mediterranean diet [aMED], recommended food score [RFS], dietary approaches to stop hypertension [DASH] and Mediterranean-DASH Intervention for Neurodegenerative Delay [MIND] diet) using the average of at least two repeated 24 h dietary assessments. 24,25 Brief descriptions of the four dietary pattern scores are presented below, and comprehensive information on the compositions and scoring methods is shown in additional file 1: ESI 26 as an adaptation of the Mediterranean diet score (MDS) to the U.S., consists of 9 food components. For alcohol, a value of 1 was given when the intake ranged between 5 g d −1 and 15 g d −1 ; otherwise, the value was 0.…”
Section: Assessment Of Dietary Patternsmentioning
confidence: 99%
“…Different studies demonstrated an association between elevated levels of total cholesterol and LDL-C and increased risk of ischemic stroke [13,14]. A high intake of sugars, including added sugars and those naturally present in honey and fruit juices, is associated with an increased risk of developing cardiovascular diseases and, specifically, stroke [15]. In recent years, several studies have linked stroke with gut dysbiosis (GD) [16].…”
Section: Causal Factorsmentioning
confidence: 99%